2016
DOI: 10.1016/j.jhep.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of a human iPSC-derived hepatocyte sheet increases survival in mice with acute liver failure

Abstract: Human iPS-HLC sheet transplantation would be a useful and reliable therapeutic approach for a patient with severe liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 35 publications
1
115
0
3
Order By: Relevance
“…Therefore, hepatocyte‐like cells (HLCs) differentiated from human induced pluripotent stem (iPS) cells, which have the potential to self‐replicate and differentiate into almost all types of cells, would be an attractive cell source . Several groups, including us, have developed hepatocyte differentiation technologies from human iPS cells and have demonstrated the therapeutic potential of human iPS‐HLCs against liver failure by using mice models of liver failure . However, the clinical application of human iPS‐HLCs has not been realized because the safety of human iPS‐HLC transplantation has not been sufficiently verified.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hepatocyte‐like cells (HLCs) differentiated from human induced pluripotent stem (iPS) cells, which have the potential to self‐replicate and differentiate into almost all types of cells, would be an attractive cell source . Several groups, including us, have developed hepatocyte differentiation technologies from human iPS cells and have demonstrated the therapeutic potential of human iPS‐HLCs against liver failure by using mice models of liver failure . However, the clinical application of human iPS‐HLCs has not been realized because the safety of human iPS‐HLC transplantation has not been sufficiently verified.…”
Section: Introductionmentioning
confidence: 99%
“…There is no ideal single cell marker by which MPCs can be distinguished from other types of cells. Recently Nagamoto et al [28] showed that the transplantation of human iPSC-derived hepatocytes sheets was the advantageous method compared to the conventional intrasplenic cell infusion method. The expression of PCLP1 was observed not only in MCs but also in podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of their study revealed that orthotopic transplantation of their engineered cell‐sheets improved liver regeneration and presented therapeutic impact on acute liver injury ( Figure ). In 2016, Nagamoto et al evaluated the therapeutic potential of human induced pluripotent stems derived hepatocyte‐like cells (iPS‐HLCs) for liver injury. The transplantation of human iPSC‐derived hepatocyte sheets into the mice with carbon tetrachloride‐induced acute liver injury showed that the transplanted sheets ameliorated the lethal acute liver damage.…”
Section: Conventional Versus Advanced Processing Technologies For LIVmentioning
confidence: 99%